Characterization of MSME outlet types in Viet Nam - Ceballos, Francisco; de Brauw, Alan; Soneja, Payal (International Food Policy Research Institute, 2023)
During 2023, researchers from Work Package 2 (WP2) of the Sustainable Healthy Diets through Food Systems Transformation (SHiFT) initiative conducted three linked surveys to learn more about micro, small, and medium enterprises (MSMEs) that currently supply foods within urban, peri-urban, and rural locations in Viet Nam and devise ways to foster their supply of sustainable nutritious foods (SNFs). The surveys had three linked goals—to better characterize the business environment in which MSMEs operate; to understand any constraints they face in selling more SNFs; and to help inform interventions with scaling potential that could increase the availability of SNFs for consumers. The first survey consisted of a listing exercise (or the “short audit”), the second survey was a longer survey targeting outlets from the listing that had a higher chance of being MSMEs and could potentially modify their food offerings, and the third survey was targeted at suppliers of those MSMEs, with the objective of identifying any potential constraints at the supplier level for expanding the offering of SNFs. The sample for the third survey was derived from the MSME sample. Ceballos et al. (2023) describe in detail the data collection efforts conducted, including sampling strategies, overall sample composition, and implementation of the three surveys. This document presents selected results from these three surveys, with a focus on the second MSME survey. The next section describes the typology of outlets enumerated in the different surveys, and the final outlet groupings used in the analyses in this note. The MSME survey results section discusses the main findings from the MSME survey in terms of general ownership characteristics, employment patterns, business skills and access to finance, food offerings, and nutrition knowledge and interest in offering more SNFs to clients, distinguishing across outlet groups and vendor clusters. The Supplier survey results section presents the main findings from the supplier survey, in terms of food offerings, the composition of their client portfolio, their level of formalization, business skills, and credit use, and their interest in selling more nutritious foods. The final section summarizes the findings and concludes.